An Application of Syndemic Theory to Identify Drivers of the Syphilis Epidemic Among Gay, Bisexual, and Other Men Who Have Sex With Men. Issue 3 (March 2018) - Ferlatte, Olivier; Salway, Travis; Samji, Hasina; Dove, Naomi; Gesink, Dionne; Gilbert, Mark; Oliffe, John L.; Grennan, Troy; Wong, Jason
Abstract : Background: We applied syndemic theory to explore the degree to which syndemic conditions explain the syphilis epidemic affecting Canadian gay and bisexual men who have sex with men (GBMSM). Methods: Data from a national survey comprising 7872 GBMSM were analyzed using multivariable logistic regression to measure associations between recent syphilis diagnosis (RSD; in previous 12 months) and the following variables: (1) sociodemographic information (sexuality, HIV status, age, income, ethnicity, relationship status), (2) antigay stigma (bullying, physical violence, sexual violence, career discrimination, health care discrimination), (3) syndemic conditions (suicidality, intimate partner violence, depression, illicit substance use, binge drinking), (4) sexual behaviors, (5) health care discrimination, and (6) the cumulative count of antigay experiences and syndemic conditions. Results: Three percent (n = 235) of GBMSM surveyed reported an RSD. Men were more likely to report an RSD if they were HIV positive (adjusted odds ratio [AOR], 6.27; 95% confidence interval [CI], 4.66–8.43). Recent syphilis diagnosis was also positively associated with career discrimination, health care discrimination, substance use, and intimate partner violence. Furthermore, prevalence of RSD increased with each additional form of stigma or syndemic condition. The odds of reporting RSD was 5.2 (95% CI, 1.0–25.9) times higher for men who reported experiencing all 4 forms of antigay stigma compared with those who reported no stigma, after adjusting for sociodemographics. Similarly, the adjusted odds of reporting RSD was 12.2 (95% CI, 2.0%–74.8%) times higher for GBMSM experiencing 5 syndemic conditions compared with those reporting no syndemic conditions. Conclusions: Evidence from this large cross-sectional study suggests that the Canadian syphilis epidemic among GBMSM is being driven by a syndemic constituted by multiple social and psychological conditions. Interventions addressing specific psychosocial health outcomes that increase the risk for syphilis should be developed and integrated within targeted sexual health services and syphilis prevention initiatives. Abstract : This study used syndemic theory to investigate associations between sexual stigma, syndemic conditions, and recent syphilis diagnoses among Canadian gay, bisexual, and other men who have sex with men.